2022
DOI: 10.1109/access.2022.3151379
|View full text |Cite
|
Sign up to set email alerts
|

Fair Power Factor Billing Under Unbalanced and Nonsinusoidal Voltage Supply

Abstract: Utilities apply an additional fee for medium and large customers with low power factors. However, unfair financial charges may occur in installations subjected to voltage unbalance and harmonic distortion. The objective of this paper is to determine the fairest PF definitions and their corresponding measurement algorithms in the case in which a constant impedance load or an induction motor is supplied with unbalanced and nonsinusoidal voltages. Fairness is defined considering that the meter (built based on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Literature [21] indicates that the effective power factor of balanced constant impedance load is not significantly affected by the unbalance of supply voltage. However, in literature [11], the power factor of three-phase induction motor with power factor reference value of 0.95 was tested under the condition of unbalance of supply voltage, and the results showed that the effective power factor would decrease with the increase of the supply voltage unbalance. For example, the power factor decreases to below 0.9 with the supply voltage unbalance increasing to 3%.…”
Section: Power Factor Calculation Of Three-phase Balanced Usermentioning
confidence: 99%
See 1 more Smart Citation
“…Literature [21] indicates that the effective power factor of balanced constant impedance load is not significantly affected by the unbalance of supply voltage. However, in literature [11], the power factor of three-phase induction motor with power factor reference value of 0.95 was tested under the condition of unbalance of supply voltage, and the results showed that the effective power factor would decrease with the increase of the supply voltage unbalance. For example, the power factor decreases to below 0.9 with the supply voltage unbalance increasing to 3%.…”
Section: Power Factor Calculation Of Three-phase Balanced Usermentioning
confidence: 99%
“…For example, effective power factor is also used in some power quality measuring instruments of FLUKE. However, the power factor calculation method based on IEEE Std 1459-2010 also has some limitations in practical applications, such as the calculation of the power factor of a three-phase balanced user and the calculation of active power [11,12]. New calculation methods based on IEEE standards have also been proposed by some scholars, such as the use of fundamental positive sequence active power [12].…”
Section: Introductionmentioning
confidence: 99%
“…The apparent power according to [11] was presented as a quantity reflecting the voltage unbalance. However, the authors in [25] showed that the related power factor penalizes customers with three-phase induction machines.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, it is possible to find works whose approaches essentially contemplate the effects of this phenomenon on devices of the power system [1]- [3], and also those in which these effects are used to verify the limitations of the indexes employed in its quantification [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…In [2], it was presented a comparison of the harmonic response of three different efficiency classes of three-phase induction motors (TIM) in the presence of voltage harmonics and unbalance with voltage variations. In [3], an investigation of the influence of unbalanced and nonsinusoidal voltages on power factor definitions and measurement algorithms was made considering a constant impedance load and a TIM.…”
Section: Introductionmentioning
confidence: 99%